Case for diagnosis. Noninfectious suppurative panniculitis induced by mesotherapy with deoxycholate, - Luana Moraes Campos; Luciane Donida Bartoli Miot; Mariângela Esther Alencar Marques; Hélio Amante Miot (Sociedade Brasileira de Dermatologia, 2020)
Abstract A 28-year-old white female patient presented with multiple erythematous-to-violaceous, painful, suppurative nodules on the buttocks and thighs that appeared after two weeks of mesotherapy with deoxycholate, caffeine, sunflower liposomes, and sinetrol for localized fat. She was treated for atypical mycobacteriosis, but with no satisfactory response after antibiotic therapy. Bacterial, mycobacterial, and fungal culture were all negative. Histopathologic examination of the biopsy showed noninfectious suppurative panniculitis. It resolved after treatment with methotrexate, prednisone, and hydroxychloroquine. This report highlights the rarity of this complication, the importance of its early recognition, and differentiation with atypical fast growing mycobacterioses.